P133 Guideline adherent therapy and reduced mortality and length of stay in adults hospitalised with exacerbations of COPD. (14th November 2013) - Short, PM; Williamson, PA; Singanayagam, A; Akram, A; Chalmers, JD; Schembri, S
Abstract : Introduction: Acute exacerbations of COPD (AECOPD) frequently cause hospitalisation and death in COPD patients. The Global Initiative for Chronic Obstructive Lung Disease (GOLD) issued recent guidelines for the treatment of COPD including that of exacerbations. GOLD guidance included the use of corticosteroids, bronchodilators, controlled oxygen therapy and appropriate use of antibiotics and non-invasive ventilation (NIV). We present an analysis of a prospective cohort of patients hospitalised with AECOPD evaluating whether compliance with GOLD COPD guidelines was associated with improved survival and reduced length of hospital stay (LoS) Methods: A prospective observational cohort study of patients admitted with AECOPD. Patients were >40 years of age, with spirometrically confirmed COPD and admitted to one of 12 UK centres between 2009–2012. We evaluated adherence to guidelines on steroid, antibiotic, bronchodilator, oxygen and NIV use. Patients' care was classified by the number of adherent guideline domains creating 5 groups; i.e. those whose care was compliant with only one guideline to those who care was compliant with all. The primary outcome was 30 day in-hospital mortality, LoS was the secondary outcome. Cox proportional hazards regression was used to calculate adjusted hazard ratios (HR) for analyses of guideline adherence. Results: 1343 patients were included in our study. There were no patients whose treatment was not compliant with any guidelines while the management of 349 individuals was fully complaint. Inpatient mortality was 6.2%. Patients whose care was compliant with one or 2 guidelines were used as the reference group for mortality analysis as only 13 patients had care compliant with a single domain. The HR for patients compliant in 3, 4 and 5 guideline domains were 0.81 (0.41–1.61) p = 0.4, 0.58 (0.30–1.13) p = 0.1, and 0.40 (0.19–0.87) p = 0.01 respectively. Figure 1 shows the relationship between survival and guideline adherence. Concordance with individual guideline domains was not associated with improved mortality. The median LoS decreased from 11 (interquartile range 6 - 15) in those who care had only one compliance to 5 (2- 10) in fully compliant care (p < 0.0001). Conclusion: Management of AECOPD that was fully concordant with GOLD guidelines was associated with significantly improved mortality and shorter hospital stays.